Tellurium-Doped Bioactive Glass Induces Ferroptosis in Osteosarcoma Cells Regardless of FSP1 - Elżbieta Pańczyszyn; Mari Lallukka; Mara Gagliardi; Valentina Saverio; Romina Monzani; Marta Miola; Enrica Verné; Marco Corazzari (Antioxidants, 2024)
Human osteosarcoma (OS) is a rare tumor predominantly affecting long bones and characterized by a poor prognosis. Currently, the first line of intervention consists of the surgical resection of primary tumors combined with radiotherapy and chemotherapy, with a profound impact on the patient’s life. Since the surgical removal of OS frequently results in a large resection of bones, the use of biomaterials to sustain the stability of the remaining tissue and to stimulate bone regeneration is challenging. Moreover, residual neoplastic cells might be responsible for tumor recurrence. Here, we explored the potential of tellurium-ion-doped bioactive glass as a novel therapeutic intervention to both eradicate residual malignant cells and promote bone regeneration. Bioactive glass (BAG) has been extensively studied and employed in the field of regenerative medicine due to its osseointegration properties and ability to improve bone tissue regeneration. We found that the incorporation of tellurium (Te) in BAG selectively kills OS cells through ferroptosis while preserving the viability of hBMSCs and stimulating their osteodifferentiation. However, the mechanism of Te toxicity is still unclear: (i) Te-BAG generates lipid-ROS through LOXs activity but not iron overload; (ii) Te-dependent ferroptosis is mediated by GPX4 down-regulation; and (iii) the anti-ferroptotic activity of FSP1 is abrogated, whose expression confers the resistance of OS to the canonical induction of ferroptosis. Overall, our data show that Te-doped bioglass could represent an interesting biomaterial with both pro-ferroptotic activity towards residual cancer cells and pro-osteoregenerative activity.